Kevin Belton's cookin' Louisiana : flavors from the parishes of the Pelican State - Belton, Kevin; Belton, Monica (Gibbs Smith, 2021)
"Kevin Belton's fourth cookbook and television series focuses on the amazing food found throughout Louisiana. The star of New Orleans Cooking with Kevin Belton heads to multiple parishes found across Louisiana to explore dishes and unique flavor profiles associated with each area of the state. Kevin Belton's Cookin' Louisiana has 78 recipes (3 from each episode of the coordinating TV series) along with a generous helping of Kevin's captivating stories and humor. Recipes include Smoked Meat Loaf with Sweet Glaze, Louisiana Fish on the Half Shell, Cane Syrup Cake, Pumpkin Soup, Fried Alligator Bites, and Shrimp Scampi Risotto."--Amazon.